SUDDEN PROGRESSIVE LOWER LIMB WEAKNESS CAUSED BY TRANSVERSE MYELITIS, MENINGITIS, AND COMMUNICANS HYDROCEPHALUS DUE TO TUBERCULOSIS: A RARE CASE REPORT - Simanjuntak, Arya Marganda; Candra, Riky; Gracia, Felicita; Maryanti, Yossi; Sucipto; Sukiandra, Riki; Juananda, Desby (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2026)
Background: This report presents a rare case of TB myelitis with concurrent TBM, emphasizing the importance of early detection and intervention due to its atypical symptoms and high risk of neurological disability. Objective: To report a rare case of tuberculous myelitis occurring concurrently with TBM and to highlight the importance of early recognition, appropriate imaging, and timely therapeutic intervention to improve neurological outcomes. Methods: A clinical case review was conducted involving a 32-year-old male presenting with progressive neurological deficits. Clinical evaluation, neuroimaging, cerebrospinal fluid (CSF) analysis, and treatment response were assessed. Management consisted of anti-tuberculosis therapy, corticosteroids, and intensive rehabilitation, with neurosurgical intervention deferred due to medical instability. Result: he patient initially developed chronic headache, fever, and cough, followed by worsening lower limb weakness, numbness, and urinary retention. Neurological examination revealed paraplegia with sensory level at T4. Imaging demonstrated hydrocephalus and pulmonary tuberculosis, while CSF analysis confirmed TBM. A diagnosis of TB myelitis with concurrent meningitis was established. Following initiation of anti-tuberculosis therapy (2RHZE/10RH), corticosteroids, and rehabilitation, the patient showed gradual neurological improvement despite the postponement of neurosurgical procedures. However, there are still few standardized protocols for diagnosing and treating TB myelitis, which calls for more research. Conclusion: Rapid diagnosis of TB myelitis, a treatable complication of CNS tuberculosis, can significantly improve patient outcomes, necessitating further research and development of new therapeutic approaches.